Exploring the conceptualisation of ‘variety’ and its effects on food intake: A mixed methods approach - Rochelle Embling (2023)
‘Food variety’ is a dietary factor with a potentially double-edged influence on consumer health. Though variety is known to support diet quality, it is also recognised as a contributing factor to overconsumption, and variety remains a concept requiring further refinement in the literature. The overarching aim of this thesis was to explore the conceptualisation of variety and its effects on food intake. Chapter 1 provides a narrative review of theoretical frameworks relevant to the concept of variety, and Chapter 2 presents a systematic review and meta-analysis of experimental studies that have explored effects of variety as a driver of meal intake. Results supported a small-to-medium effect, but highlighted significant heterogeneity across studies. Chapter 3 includes findings from two qualitative studies focussed on the consumer understanding of variety. Results showed that consumers have an awareness of variety when discussing hypothetical preferences, but that participants generally defined ‘variety’ only in the context of the whole diet. Chapters 4 and 5 further explored effects of variety within foods, specifically when measuring portion size selection using a novel online tool. Though no significant differences were found across levels of variety, key methodological issues specific to investigating effects of composite foods were highlighted. Chapter 6 reports effects of dietary variety on body weight using prospective data from the UK Biobank. Dietary variety was a significant predictor of portion size. There was also some evidence of a significant, negative association between dietary variety and body weight, though portion size as a mediator and energy density as a moderator did not significantly influence this relationship. Overall, this thesis supports variety as a robust driver of food intake. Results provide novel insight into the conceptualisation of variety from a researcher and consumer perspective, highlighting implications for tailoring future research focussed on variety to the modern eating environment.